Knowledge, attitudes, beliefs and barriers of healthcare professionals and adults ≥ 65 years about vaccine-preventable diseases in Spain: the ADult Vaccination drIverS and barriErs (ADVISE) study - Esther Redondo Margüello; Antoni Trilla; Ignacio L. B. Munguira; Almudena Jaramillo López-Herce; Manuel Cotarelo Suárez (Taylor & Francis Group, 2022)
Since 2018, Spanish National Immunization Guidelines include vaccination recommendations for adults ≥65 years. To determine whether health-care professionals and the ≥65 years target group value the need for these recommendations, a cross-sectional study was conducted to capture and describe their knowledge, attitudes, beliefs and behaviors about vaccination. Online surveys were administered to representative groups of general practitioners (GPs), primary care nurses and adults ≥65 years from six major cities (and surrounding rural areas) in Spain. Main topics were attitudes and awareness of vaccines, perceptions about vaccination in adults ≥65 years, and impact of the COVID-19 pandemic on vaccination uptake. A total of 286 health-care professionals (185 GPs, 101 nurses) and 400 adults aged ≥65 years participated in the survey. GP and nurse groups agreed strongly about the importance of influenza and pneumococcal vaccination in the target population. Longer patient visit times were identified as a key factor toward promoting vaccination. The ≥65 years sample group, especially those ≥75+ years and/or with chronic diseases, was reasonably positive about the effectiveness and benefits of vaccines. Lower vaccination rates for the pneumococcal than influenza vaccine (29% vs. 80%) in the ≥65 years sample group suggest that efforts are needed to improve pneumococcal vaccine uptake. Aligning with other published works, GPs have a key role in promoting vaccination in the target population. The COVID-19 pandemic appears to have heightened awareness about the importance of vaccination among health-care professionals and adults ≥65 years.